2016
DOI: 10.1080/00913847.2016.1228421
|View full text |Cite|
|
Sign up to set email alerts
|

Rapid weight gain in professional boxing and correlation with fight decisions: analysis from 71 title fights

Abstract: Although correlations between WG, WD and boxing performance were not found, single cases with an alarming high WG and WD were noted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 30 publications
0
29
0
Order By: Relevance
“…In most 239 combat sports, it was reported that the majority of weight lost in 240 the 24 h before weigh-in was recovered prior to competition and 241 the majority of weight lost was typically regained 7 days 242 following weigh-in ( The present study sought to investigate the strategies used for tasks, 6,12,17 or at least no increase in competitive success. 24,25 We 315 also provide further evidence that weight loss practices in MMA 316 may be more extreme than other combat sports 6 with MMA 317 reporting significantly greater weight loss than other combat 318 sports within two weeks and 24 h of weighing-in (Table 3). The percentage of TKD athletes also reported competing at the 330 professional level and the magnitude of weight loss in TKD was 331 similar to other combat sports assessed ( Table 2 and 3).…”
mentioning
confidence: 73%
“…In most 239 combat sports, it was reported that the majority of weight lost in 240 the 24 h before weigh-in was recovered prior to competition and 241 the majority of weight lost was typically regained 7 days 242 following weigh-in ( The present study sought to investigate the strategies used for tasks, 6,12,17 or at least no increase in competitive success. 24,25 We 315 also provide further evidence that weight loss practices in MMA 316 may be more extreme than other combat sports 6 with MMA 317 reporting significantly greater weight loss than other combat 318 sports within two weeks and 24 h of weighing-in (Table 3). The percentage of TKD athletes also reported competing at the 330 professional level and the magnitude of weight loss in TKD was 331 similar to other combat sports assessed ( Table 2 and 3).…”
mentioning
confidence: 73%
“…As weight-cutting is done in preparation for competition it is essential to understand the influence on performance. Studies correlating weight manipulation strategies to competitive outcomes in boxing have reported greater weight loss and regain to improve [32,33,34] or have no influence on competitive success [35,36]. The results of laboratory-based trials investigating the effects of weight-cutting on varying aspects of exercise performance are also mixed.…”
Section: Weight-cutting and Performancementioning
confidence: 99%
“…Whilst there appears to be little effect of AWL/RWL on winning or losing in striking inclusive sports (Daniele, Weinstein, Wallace, Palmieri, & Bianco, 2016;Kirk, Langan-Evans, & Morton, 2020;Reale, Cox, Slater, & Burke, 2017), there is some support for this practice being predictive of success in grappling only events (Reale, Cox, Slater, & Burke, 2016;Wroble & Moxley, 1998).…”
Section: Introductionmentioning
confidence: 99%